2008
DOI: 10.1097/olq.0b013e318154bdb2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Sexually Transmitted Infection Among Newly Incarcerated Females

Abstract: The prevalence of STI in this jail population is high. Incarceration represents a unique opportunity to evaluate and treat this underserved population. Predictors of infection are limited and infection is common; therefore, routine screening should be considered in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
3
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 18 publications
5
32
3
7
Order By: Relevance
“…However, previous studies on this topic have revealed similar findings for women in prisons. 13,15,16 Further investigation is needed to determine the applicability of the results to all incarcerated women.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, previous studies on this topic have revealed similar findings for women in prisons. 13,15,16 Further investigation is needed to determine the applicability of the results to all incarcerated women.…”
Section: Discussionmentioning
confidence: 95%
“…12 African American and Hispanic women, regardless of income status, are at highest risk of unintended pregnancy by not using contraception regularly. 12,13 Finally, a study reported that women from low-income populations who specifically planned on using oral contraceptives or condoms postpartum were less likely to actually use that method of contraception or any contraception than those who chose longer-term contraceptive methods. 14 Previous research has found that oral contraceptive users tend to include women from higher socioeconomic status (SES) and with lower sexually transmitted disease (STD) risks.…”
Section: Introductionmentioning
confidence: 97%
“…African American and Hispanic women as well as women with incomes below poverty are at highest risk for unintended pregnancy because of high rates of inconsistent contraceptive use (Radecki & Bernstein, 1990;Willers et al, 2008).…”
mentioning
confidence: 99%
“…Incarcerated women live in the midst of epidemics of HIV and sexually transmitted infections (Willers et al, 2008). Earlier studies have documented that incarcerated women use condoms infrequently (Clarke et al, 2006;El-Bassel et al, 1995).…”
mentioning
confidence: 99%